Keep that web afloat. - Hogge, Becky (New Statesman, 2007)
This article reports the author's experience with web servers and the technical requirements that maintain the ever-growing internet. She contrasts the quiet and reserved technicians, who keep everyone's site up and running, with the extroverted, creative types, like John Perry Barlow, who champion it.